THE STUDY FOR REGIONAL RETAIL PHARMACEUTICAL MARKET - O. V. Sokolova; L. I. Lavrentyeva; K. S. Alekseyeva (Фармация и фармакология (Пятигорск))
Pharmacy organizations are an element of regional pharmaceutical market infrastructure formation. They have different character and activity type, organizational and legal forms, types of properties. The revelation of the features of retail pharmaceutical market of Yaroslavl oblast was the purpose of the study. The analysis of the data of regional department of Federal Service on Surveillance in Healthcare and Social Development of Russian Federation  n Yaroslavl oblast in the beginning of 2014 showed that there are 137 acting commercial entities, which have licenses for pharmaceutical activity. The region has 487  pharmacy organizations which implement pharmaceutical activity of state (14.6%), municipal (7.4%), and private (78.0%) forms of ownership. Some companies function in Yaroslavl (43.9%) and Rybinsk (22.4%) municipal district. The analysis of organization and legal forms revealed that 48.9% of pharmacy organizations are registered as ltd, 14.6% are state, and 14.2% are private entrepreneurs, public limited companies amount to 10.9%, the rest pharmacy organizations are included into municipal unitary enterprises and private limited companies – 7.39% and 4.1% correspondingly. The structure of retail market is represented by single pharmacy organizations (51.1%) as well as organizations joined into pharmacy chains from two and more PO (48.9%). The share of commercial entities which include one PO amounted to 14.4% of all PO. Share of pharmacy chains (42.3%) which include from 2 to 9 PO are 46.8% of all PO. Pharmacy chains, which have more than 9 retails spots amount to 6.6% of the total number of commercial entities. 38.8% of PO function within them. Pharmacy chains prevalence (42.3%), joined into 9 PO; pharmacy chains, which have more than 9 PO, and include state sector PO (14.6%) are the features of the regional market.